2021
DOI: 10.1039/d1ra05123g
|View full text |Cite
|
Sign up to set email alerts
|

Ductile keratin films from deep eutectic solvent-fractionated feathers

Abstract: In the present study, cross-linked keratin films were prepared using deep eutectic solvent (DES) fractionated feathers as a raw material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 45 publications
2
18
0
Order By: Relevance
“…Previously, the Mw of high- and low-Mw keratin fractions were analyzed with matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF) revealing that the DES-treated keratin consisted of many different-sized keratin fragments. 11 Similar observations of keratin molecular weight distributions have also been reported after N -methylmorpholine N -oxide (NMMO) treatment for feathers. 13 Although the low Mw fraction was initially water soluble in the presence of diluted DES components, the low-Mw keratin fraction was not completely soluble in pure water or in the used buffers after dialyzing and freeze-drying.…”
Section: Resultssupporting
confidence: 65%
See 3 more Smart Citations
“…Previously, the Mw of high- and low-Mw keratin fractions were analyzed with matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF) revealing that the DES-treated keratin consisted of many different-sized keratin fragments. 11 Similar observations of keratin molecular weight distributions have also been reported after N -methylmorpholine N -oxide (NMMO) treatment for feathers. 13 Although the low Mw fraction was initially water soluble in the presence of diluted DES components, the low-Mw keratin fraction was not completely soluble in pure water or in the used buffers after dialyzing and freeze-drying.…”
Section: Resultssupporting
confidence: 65%
“…Previous studies show that when feathers are processed with DES, ionic liquid, or N -methylmorpholine N -oxide, the keratin loses its ordered structure. ,, Moreover, in these processes, keratin degrades into different sized fragments and even into small peptides and amino acids , leading to the loss of its mechanical properties. However, our previous work showed that together with a plasticizer, the low molecular weight keratin fraction was able to form a dense and uniform film network with decreased water vapor permeability . Hence, we speculate that together with lignocellulosic building blocks that provide the mechanical strength, the acquired keratin fraction having different amino acids with different chemical structures could provide properties lacking from these materials.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…In particular, keratin solution should be cross-linked by an active ingredient or via stimulating the development of disulfide bridges in order to create the hydrogel [190]. In this regard, cross-linkers include glutaraldehyde [191], transglutaminase [192], dialdehyde [193], ethylene glycol diglycidyl ether [194], glyoxal [195], and formaldehyde [196]. In addition, oxidized cellulose nanocrystal serves as both a reinforcing agent and a keratin cross-linker.…”
Section: Keratin-based Hydrogelsmentioning
confidence: 99%